THE CORRELATION AMONG PARENTS’ EDUCATION, PARENTS’ INVOLVEMENT AND TWELFTH GRADERS’ ENGLISH ACHIEVEMENT - Dale Karnegi; Tahrun Tahrun; Mulyadi Mulyadi (Esteem Journal of English Education Study Programme, 2022)
The objective of this research aims to find out whether or not significant correlation between parents’ education and the parents’ involvement, parents’ education and the twelfth graders’ English achievement , parents’ involvement and the twelfth graders’ English achievement , and parents’ education parent’s involvement and the twelfth graders’ English achievement of SMAN 5 Prabumulih academic year of 2019/2020 which consisted of six classes. A quantitative method used in this research also used a stratified random sampling methods. There are two kinds of data will be analyzed. The first is questionnaire and the second is the data of documents. There was any significant influence because significant output (0,000) was lower than the mean of significant influence at 0.05 levels. It could be concluded that there were any significant influence of parents’ education and parents’ involvement toward English achievement.